The Poor and Justice: Implementation of Legal Aid for the Poor in Indonesia (Problems and Solutions) - Hapsari, Judith Prima (Faculty of Law Universitas Negeri Semarang, 2021)
One manifestation of justice or equality before the law is the existence of legal assistance for every citizen involved in legal problems, without exception the poor. The legal problems that ensnare many poor people or groups are currently increasing complex. Legal aid is a human right of all people, which is not given by the state and is not a mercy from the state, but is also the responsibility of the state in realizing equality before the law, access to justice, and fair trial. Therefore, the government made and ratified a regulation that regulates legal aid, namely Law Number 16 of 2011 concerning Legal Aid. This research is intended to analyze the implementation of legal aid for the poor communities in the context of access to justice in Indonesia.